Research and Modelling of Noise of the Central Part of Panevėžys City - Pranas Baltrėnas; Egidijus Petraitis; Tomas Januševičius (The Baltic Journal of Road and Bridge Engineering)
Panevėžys city is divided into three parts – Southern, Northern and Central. Noise level in the central part of Panevėžys city is discussed in this paper. Noise level at streets is measured at different time of the day. Noise level modelling is carried out in the central part of Panevėžys. Modelling results are compared to measured ones. The inadequacy of measured and modelled results d being up to 10%, assumption is made that the modelled and the measured results correlate, and noise level in residential areas as well as at streets is analyzed according to the results of modelling in the day – time and by night. The main sources of noise and the highest noise level zones where the inhabitants are affected by the increased noise level most are revealed.